Down the brain drain: a rapid review exploring physician emigration from West Africa - Tega Ebeye; HaEun Lee (BMC, 2023)
Abstract Background The emigration of physicians from low- and middle-income countries (LMICs) to high-income countries (HICs), colloquially referred to as the "brain drain", has been a topic of discussion in global health spheres for years. With the call to decolonize global health in mind, and considering that West Africa, as a region, is a main source of physicians emigrating to HICs, this rapid review aims to synthesize the reasons for, and implications of, the brain drain, as well as recommendations to mitigate physician emigration from West African countries to HICs. Methods A literature search was conducted on PubMed, EMBASE and The Cochrane Library. Main inclusion criteria were the inclusion of West African trained physicians' perspectives, the reasons and implications of physician emigration, and recommendations for management. Data on the study design, reasons for the brain drain, implications of brain drain, and proposed solutions to manage physician emigration were extracted using a structured template. The Hawker Tool was used as a risk of bias assessment tool to evaluate the included articles. Results A total of 17 articles were included in the final review. Reasons for physician emigration include poor working conditions and remuneration, limited career opportunities, low standards of living, and sociopolitical unrest. Implications of physician emigration include exacerbation of low physician to population ratios, and weakened healthcare systems. Recommendations include development of international policies that limit HICs' recruitment from LMICs, avenues for HICs to compensate LMICs, collaborations investing in mutual medical education, and incorporation of virtual or short-term consultation services for physicians working in HICs to provide care for patients in LMICs. Conclusions The medical brain drain is a global health equity issue requiring the collaboration of LMICs and HICs in implementing possible solutions. Future studies should examine policies and innovative methods to involve both HICs and LMICs to manage the brain drain.